Do financial ratios affect stock prices in the consumer non-cyclical sector? - Ida Rokhyani; Saniman Widodo; Mella Katrina Sari (Sebelas Maret Business Review, 2023)
Maintaining a company's position among its competitors requires significant investment funds. The capital market is an alternative for companies to overcome investment funding constraints. Capital market performance is reflected in the Stock Index, which describes stock price movements. Fluctuating stock index movements indicate that there are things that influence the direction of the index. This research method uses secondary data sourced from the official website of the Indonesian Central Securities Depository (Kustiodian Sentral Efek Indonesia-KSEI), the Indonesian Stock Exchange (Bursa Efek Indonesia-BEI), the Financial Services Authority (Otoritas Jada Keuangan-OJK), and www.investing.com. Thirty-three companies operating in the non-cyclical consumer sector and listed on the Indonesian Sharia Stock Index (ISSI) for the 2018-2022 period are the sample in this research. Furthermore, the approach used in this research is a quantitative method with multiple linear regression analysis tools processed using the SPSS 25.00 program. The results have a positive and insignificant effect, namely the Current Ratio (CR) and Debt to Equity Ratio (DER). On the contrary, Earning Per Share (EPS) and Return On Equity (ROE) are factors that have a positive and significant influence on share prices in the non-cyclical consumer sector recorded in the Indonesian Sharia Stock Index (ISSI) for the 2018-2022 period.